Application of Soundscape Design Elements in Urban Streetscape Design - Hong, Jooyoung; Jeon, Jin Yong (AESOP, 2012)
This study explores how soundscape design elements can improve the quality of urban streetscapes by mitigating negative noise perceptions. Laboratory experiments evaluated the impact of road traffic noise as a negative element and natural sounds such as water and birdsong as positive elements. The experiments were conducted under three conditions—visual-only, audio-only, and combined audio-visual—using semantic differential scales and numerical ratings. The results demonstrate that integrating natural sounds into urban design enhances the perception of sound environments, highlighting the value of soundscape principles for creating more pleasant and sustainable urban spaces.
Book of proceedings : AESOP 26th Annual Congress 11-15 July 2012 METU, Ankara
Keywords: soundscape; urban streetscape; noise perception; traffic noise; natural sounds; audio-visual environment